Introduction to stand alone data converters review, analysis and design orientation - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2020)
This paper includes a basic review, analysis, and interesting insights, oriented to designers when power consumption is a critical constraint, of Stand-Alone Data Converters. These data converters are an indispensable part of the analog design technique and the only bridge to establish an adequate communication link between analog and digital devices. In fact, this article is dedicated to showing the principal types of the analog-to-digital converters (ADC) and digital-to-analog converters (DAC) families of data converters popular in modern analog design techniques. In fact, these data converters are also cost-effective devices because of the huge number of existing and newly developed solutions with their significant practical features providing more relevant applications in specific type of ADC or DAC process. The overview of data conversion, ADC and DAC data converters, communication bus to Micro Controller Units (MCU), and benefits of data conversion are described.Â Â